2015
DOI: 10.1002/asi.23480
|View full text |Cite
|
Sign up to set email alerts
|

Social scientists' satisfaction with data reuse

Abstract: Much of the recent research on digital data repositories has focused on assessing either the trustworthiness of the repository or quantifying the frequency of data reuse. Satisfaction with the data reuse experience, however, has not been widely studied. Drawing from the information systems and information science literature, we developed a model to examine the relationship between data quality and data reusers' satisfaction. Based on a survey of 1,480 journal article authors who cited Inter-University Consorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 60 publications
(157 reference statements)
0
81
0
Order By: Relevance
“…Several recent studies have investigated data reuse practices and behaviors in the social sciences (Daniels, Faniel, Fear, & Yakel, 2012;Faniel, Kriesberg, & Yakel, 2012;Faniel, Kriesberg, & Yakel, 2016;Niu, 2009;Yoon, 2014bYoon, , 2016Yoon, , 2017 as part of a broader drive to understand data practices within the social sciences. While these studies have captured some of the contexts and characteristics of social science data reuse by focusing on specific aspects of data reuse practices, which may overlap with other disciplinary contexts, fewer studies have used theoretical approaches or models to explain social scientists' data reuse behaviors.…”
Section: Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations
“…Several recent studies have investigated data reuse practices and behaviors in the social sciences (Daniels, Faniel, Fear, & Yakel, 2012;Faniel, Kriesberg, & Yakel, 2012;Faniel, Kriesberg, & Yakel, 2016;Niu, 2009;Yoon, 2014bYoon, , 2016Yoon, , 2017 as part of a broader drive to understand data practices within the social sciences. While these studies have captured some of the contexts and characteristics of social science data reuse by focusing on specific aspects of data reuse practices, which may overlap with other disciplinary contexts, fewer studies have used theoretical approaches or models to explain social scientists' data reuse behaviors.…”
Section: Problem Statementmentioning
confidence: 99%
“…Easy access to data was one of the most influential factors in determining social scientists' satisfaction with data reuse (Faniel, Kriesberg, & Yakel, 2016). Data repositories have a long history in social science, and they are known to support easy access to and reuse of available data through value-adding activities (Daniels, Faniel, Fear, & Yakel, 2012;Yoon, 2014a).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on results from a study of users' perceptions of data quality, Wang and Strong (1996) identified four dimensions of data quality: 1) intrinsic, referring to the accuracy and credibility of the data; 2) contextual, or the relevancy of the data to the user's goals; 3) representational, relating to the ability to interpret and use the data; and 4) accessibility, or the ability to obtain the data. A more recent study conducted by Faniel, Kriesberg, and Yakel (2015) to determine the factors that elicit social science researchers' satisfaction with data reuse found that users associate data quality with attributes that align with Wang and Strong's quality dimensions. They include completeness (contextual), accessibility (accessibility), ease of operation (representational), and credibility (intrinsic) of the data.…”
Section: Data Quality Standardsmentioning
confidence: 99%